Detection of Stress using Short-Time Energy Dispersion of Speech Signal - Cícha, Jan; Horský, Pavel; Haisman, David (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2025)
Our research shows that it is possible to identify stress from a speech signal using energy factors. The proposed method is based on the dispersion of short-time signal energy. The results obtained for full speech and voiced speech are presented. T he voiced parts of speech were extracted from continuous speech by means of center clipping algorithm with optimized parameters . The voiced parts provide better results.
Keywords: speech signal; short-time energy; speech under stress